DESEMPENHO AGRONÔMICO DE CULTIVARES DE SOJA DE DIFERENTES CICLOS - Lemos, Leandro Borges; Zapparoli, Rodolfo Alexandre; Farinelli, Rogério; Cavariani, Cláudio (REVISTA DE AGRICULTURA, 2015)
DESEMPENHO AGRONÔMICO DE CULTIVARES DE SOJA DE DIFERENTES CICLOS